Burden of tuberculosis trends in a Brazilian southern state - Pamela Nogueira Silva Vilela; Ione Jayce Ceola Schneider; Eliane Traebert; Jefferson Traebert (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2018)
ABSTRACT: Introduction: The burden of tuberculosis has been scarcely explored in developing countries. Objective: To estimate the trend of the burden of tuberculosis in the state of Santa Catarina, southern Brazil, from 2007 to 2011. Methods: Epidemiological time-series study on tuberculosis notifications and deaths reported in the Disease Notification System and the Mortality Information System between 2007 and 2011. Crude rates of Disability-Adjusted Life Years (DALY) and subcomponents were calculated and standardized by gender and age groups. Segmented linear regression was used to estimate the trends for burden of tuberculosis during the study period. Results: There were 696 deaths and 8,598 notifications during the study period. The highest rate was found in 2009, with 91.8 DALY/100,000 inhabitants, and the lowest in 2007, with 67.2 DALY/100,000 inhabitants. The highest burden was among men in economically active age groups. The study showed a non-significant increase of 3.8% per year in DALY rates. Conclusion: The burden of tuberculosis remained stable in Santa Catarina, Brazil between 2007 and 2011.